FOREST FIRE RISK FORECAST FOR THE STATE OF SANTA CATARINA DUE TO CLIMATE CHANGES - Ho, Tatiane Lima; Batista, Antonio Carlos; Tetto, Alexandre França (Floresta, 2017)
Forest plays a fundamental role in the environmental balance, mainly in the regulation of the climate, main variable that interferes in the propagation of fire in a forest fire. Climate change is caused by astronomic, natural and anthropogenic factors, the latter being primarily responsible for the change in the fire regime. There is a projection that there will be climate changes over the next 100 years, which will result in an impact on forest ecosystems. Therefore, this study aimed to was to determine, by decade, the Forest Fire Risk Zone Mapping (FFRZM) for the state of Santa Catarina by considering the average of two scenarios for the increase of the temperature of the Earth until 2100 (1 °C for the best-case scenario and 2.2 ºC for the worst-case scenario) that were foreseen by the Intergovernmental Panel on Climate Change (IPCC) in 2013. For this purpose, eight variables classified according to fire risk and integrated in a weighting model were used. The results showed that, for both scenarios, there will be an increase of 11.48% in the best-case scenario and 10.83% in the worst-case scenario in the extreme risk class from 2010 to 2100. For the low risk one, we estimate that there will be an increase of 8.13% in the best-case scenario and 11.62% in the worst-case scenario. The study reveals that if there is an increase in the temperature of the Earth, there may be an increase in the number of forest fire occurrences in the state of Santa Catarina for both scenarios. Thus, it is necessary a greater action on the prevention and combat in the areas defined as extreme risk. Keywords: fuel load, Monte Alegre Formula, topography, population density, road system. Resumo Previsão do risco de incêndios florestais para o estado de Santa Catarina em função das mudanças climáticas A floresta desenvolve um papel fundamental no equilíbrio ambiental, principalmente, na regulação do clima, variável principal que interfere na propagação do fogo em um incêndio florestal. As mudanças climáticas são causadas por fatores astronômicos, naturais e antropogênicos, sendo este último o principal responsável pela mudança no regime do fogo. Há uma projeção de que haverá alterações climáticas nos próximos 100 anos, o que ocasionará um impacto nos ecossistemas florestais. O objetivo desse trabalho foi determinar, por decênio, o Zoneamento de Risco de Incêndios Florestais (ZRIF) para o estado de Santa Catarina, considerando a média de dois cenários de aumento da temperatura da Terra até 2100 (1 ºC para o melhor cenário e 2,2 ºC para o pior cenário) previstos pelo Painel Intergovernamental de Mudanças Climáticas (IPCC) em 2013. Para isso, foram utilizadas oito variáveis, que foram classificadas em função do risco de incêndios e integradas em um modelo de ponderação. Os resultados mostraram que, para ambos os cenários, haverá um aumento na classe de risco extremo de 11,48% no melhor cenário e de 10,83% no pior cenário no período de 2010 a 2100. Para o risco baixo, estima-se que haverá um aumento de 8,13% no melhor cenário e de 11,62% no pior cenário. Conclui-se que, caso haja aumento na temperatura da Terra, poderá haver um aumento no número de ocorrências de incêndios florestais no estado de Santa Catarina para ambos os cenários, Sendo necessária uma maior ação de prevenção e combate nas áreas definidas como risco extremo. Palavras-chave: material combustível, Fórmula de Monte Alegre, topografia, densidade demográfica, sistema viário.